PENERAPAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG BENTUK ALJABAR - Pujiati . (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
APPLICATION OF STUDENT TEAM ACHIEVEMENT DIVISION MODEL TO IMPROVEMENT OF STUDENTS’ ACHIEVEMENT IN MATHEMATICS ABOUT ALGEBRAIC FORMThe Research used a Classroom Action Research (CAR) approach which was carried out collaboratively and in two cycles. The aim of the  research is to find out the improvement of students ‘achievement   in mathematics about algebraic form in class VII D through the application of the learning model Student Team Achievement Division (STAD). The subjects of this study were 33 students of class VII D at SMP Negeri 13 Bogor, with a composition of 19 female students and 14 male students. The results showed that the average value of learning outcomes in the first cycle obtained a value of 75.1 with a percentage of 66.7%; while the second cycle obtained an average value of 89 with a percentage of 91%, there was an improvement of student, or an improvement of completeness by 24.3%. Likewise, the results of student observations showed an increase in the participation and activity of students by obtaining an average value of 75.38% in the first cycle, while the second cycle reached 88.76%. The conclusion of this Research is that the application of the Student Team Achievement Division (STAD) learning model can improve mathematics learning outcomes in algebraic form material.